Individual health trainers to support health and well-being for people under community supervision in the criminal justice system: the STRENGTHEN pilot RCT - Lynne Callaghan; Tom P Thompson; Siobhan Creanor; Cath Quinn; Jane Senior; Colin Green; Annie Hawton; Richard Byng; Gary Wallace; Julia Sinclair; Amy Kane; Emma Hazeldine; et al. (NIHR Journals Library, 2019)
Background: Little is known about the effectiveness or cost-effectiveness of interventions, such as health trainer support, to improve the health and well-being of people recently released from prison or serving a community sentence, because of the challenges in recruiting participants and following them up. Objectives: This pilot trial aimed to assess the acceptability and feasibility of the trial methods and intervention (and associated costs) for a randomised trial to assess the effectiveness and cost-effectiveness of health trainer support versus usual care. Design: This trial involved a pilot multicentre, parallel, two-group randomised controlled trial recruiting 120 participants with 1 : 1 individual allocation to receive support from a health trainer and usual care or usual care alone, with a mixed-methods process evaluation, in 2017-18. Setting: Participants were identified, screened and recruited in Community Rehabilitation Companies in Plymouth and Manchester or the National Probation Service in Plymouth. The intervention was delivered in the community. Participants: Those who had been out of prison for at least 2 months (to allow community stabilisation), with at least 7 months of a community sentence remaining, were invited to participate; those who may have posed an unacceptable risk to the researchers and health trainers and those who were not interested in the trial or intervention support were excluded. Interventions: The intervention group received, in addition to usual care, our person-centred health trainer support in one-to-one sessions for up to 14 weeks, either in person or via telephone. Health trainers aimed to empower participants to make healthy lifestyle changes (particularly in alcohol use, smoking, diet and physical activity) and take on the Five Ways to Well-being [Foresight Projects. Mental Capital and Wellbeing: Final Project Report. 2008. URL: www.gov.uk/government/publications/mental-capital-and-wellbeing-making-the-most-of-ourselves-in-the-21st-century (accessed 24 January 2019).], and also signposted to other options for support. The control group received treatment as usual, defined by available community and public service options for improving health and well-being. Main outcome measures: The main outcomes included the Warwick-Edinburgh Mental Well-being Scale scores, alcohol use, smoking behaviour, dietary behaviour, physical activity, substance use, resource use, quality of life, intervention costs, intervention engagement and feasibility and acceptability of trial methods and the intervention. Results: A great deal about recruitment was learned and the target of 120 participants was achieved. The minimum trial retention target at 6 months (60%) was met. Among those offered health trainer support, 62% had at least two sessions. The mixed-methods process evaluation generally supported the trial methods and intervention acceptability and feasibility. The proposed primary outcome, the Warwick-Edinburgh Mental Well-being Scale scores, provided us with valuable data to estimate the sample size for a full trial in which to test the effectiveness and cost-effectiveness of the intervention. Conclusions: Based on the findings from this pilot trial, a full trial (with some modifications) seems justified, with a sample size of around 900 participants to detect between-group differences in the Warwick-Edinburgh Mental Well-being Scale scores at a 6-month follow-up. Future work: A number of recruitment, trial retention, intervention engagement and blinding issues were identified in this pilot and recommendations are made in preparation of and within a full trial. Trial registration: Current Controlled Trials ISRCTN80475744. Funding: This project was funded by the National Institute for Health Research Public Health Research programme and will be published in full in Public Health Research; Vol. 7, No. 20. See the National Institute for Health Research Journals Library website for further project information.